PHYTOCHEMICAL INVESTIGATION OF CHENOPODIUM MURALE (FAMILY: CHENOPODIACEAE) CULTIVATED IN IRAQ, ISOLATION AND IDENTIFICATION OF SCOPOLETIN AND GALLIC ACID - Ahmed, Omer H; Hamad, Maha N; Jaafar, Noor S (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The aim of our study was to investigate chemical constituents of leaves of Chenopodium murale since no phytochemical investigation had been done previously in Iraq. Methods: Leaves of C. murale were macerated in absolute methanol for 2 days and fractionated by petroleum ether, chloroform, ethyl acetate, and n-butanol. The ethyl acetate fraction was analyzed by high-performance liquid chromatography (HPLC) and high-performance thin-layer chromatography (HPTLC) for its phenolic acid and coumarins contents. Coumarin derivative and phenolic acid were isolated from this fraction and identified by gas chromatography/mass spectrometry, infrared, ultraviolet, HPLC, and HPTLC. Results: The different chromatographic and spectroscopic results revealed the presence of gallic acid and coumarin. Conclusion: The results of the current study showed the presence of scopoletin and gallic acid in the ethyl acetate fraction of C. murale.